2019
DOI: 10.1111/jdv.15957
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of dupilumab for the treatment of prurigo nodularis in a French multicenter adult cohort of 16 patients

Abstract: The notion that it is related to M. lepromatosis may be true according to some authors. However, others showed that the correlation is not that strong, looking at leprosy clinical types in different countries 6 ; M. lepromatosis may resemble M. leprae in causing different manifestations depending on the host immunity. 2 From the group around Rea and Modlin, Maria Achoa reported at the World Congress Dermatology in Milano that of their Mexican patients with lepra bonita, the majority was indeed infected with M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 9 publications
5
41
1
3
Order By: Relevance
“…In addition to our case, a total of 24 prurigo nodularis patients have recently been successfully treated with dupilumab (Table 1) and another 16 were treated with dupilumab in an efficacy study by a French group (although there may be some overlap with previously reported patients) [9]. In contrast to our patient, relief from itching was much more rapid in these cases, with improvement within a few weeks [10][11][12][13][14].…”
supporting
confidence: 50%
See 1 more Smart Citation
“…In addition to our case, a total of 24 prurigo nodularis patients have recently been successfully treated with dupilumab (Table 1) and another 16 were treated with dupilumab in an efficacy study by a French group (although there may be some overlap with previously reported patients) [9]. In contrast to our patient, relief from itching was much more rapid in these cases, with improvement within a few weeks [10][11][12][13][14].…”
supporting
confidence: 50%
“…After a full medical examination (including extensive laboratory parameters, sonography of the abdomen, skin biopsies and chest x-ray) no conclusive diagnosis was reached. Based on clinical signs and symptoms with high total IgE levels and an elevated value of the Erlangen atopy score (9) the patient was diagnosed with late onset AD. Treatment with very potent topical corticosteroids (0.5 mg/g clobetasol propionate), narrow band UVB irradiation and oral antihistamines was initiated.…”
mentioning
confidence: 99%
“…In the literature, some cases of PN were reported that were successfully treated with dupilumab, showing efficacy in reducing the itch (Beck, Yang, Sekhon, Bhutani, & Liao, ; Calugareanu et al, ; Ferrucci, Tavecchio, Berti, & Angileri, ; Mollanazar, Elgash, Weaver, et al, ; Napolitano et al, ; PH1 & JO2, ; Tanis, Ferenczi, & Payette, ; Zhai et al, ).…”
mentioning
confidence: 99%
“…Der Fallbericht einer IgG4-assozierten Erkrankung mit pruriginösen Nodi zeigte, dass ein erhöhter Prozentsatz an Th2-Zellen und eine Erhöhung der IL-4und IL-13-Produktion auch bei dieser Erkrankung vorliegen kann [7]. Eine rezente Untersuchung zeigte eine gesteigerte [9]. Im Gegensatz zu unserer Patientin war das subjektive Ansprechen (Reduktion des Pruritus) in den meisten Fällen deutlich früher zu beobachten [10][11][12][13][14].…”
Section: Clinical Letterunclassified